2018
DOI: 10.1103/physreve.97.042611
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interaction between dissimilar colloids at fluid interfaces

Abstract: The electrostatic interaction between two nonidentical, moderately charged colloids situated in close proximity of each other at a fluid interface is studied. By resorting to a well-justified model system, this problem is analytically solved within the framework of linearized Poisson-Boltzmann density functional theory. The resulting interaction comprises a surface and a line part, both of which, as functions of the interparticle separation, show a rich behavior including monotonic as well as nonmonotonic vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…As expected, the interfacial tension depends only on the properties of the two fluid media and not on any plate properties. Consequently, the expression for γ 1,2 does not differ from what one obtains for plates with constant surface charge densities [53].…”
Section: Interaction Energiesmentioning
confidence: 64%
See 3 more Smart Citations
“…As expected, the interfacial tension depends only on the properties of the two fluid media and not on any plate properties. Consequently, the expression for γ 1,2 does not differ from what one obtains for plates with constant surface charge densities [53].…”
Section: Interaction Energiesmentioning
confidence: 64%
“…( 13) vanish except for the last term, i.e., τ. Therefore, in this limit ω τ (L) stays finite unlike what one observes for constant charge boundary condition [50,53]. Using the relation ∞ n=1,3,...…”
Section: Interaction Energiesmentioning
confidence: 66%
See 2 more Smart Citations
“…It has been shown that in this case the linearization of the Poisson-Boltzmann (PB) theory is applicable [21]. Recent studies, directed towards the opposite limit of small inter-particle separations, have been performed within the linearized PB theory [22][23][24] or by considering a flat plate geometry [22,24,25] in order to simplify the problem. Whereas the former approximation is often violated at short separations, the latter represents the ideal situation of a contact angle of exactly 90 • and the absence of particle curvature.…”
Section: Introductionmentioning
confidence: 99%